2022
DOI: 10.33367/psi.v7i2.2315
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Self-Efficacy, Emotional Intelligence, and Parental Social Support with Learning Motivation of University Students in Distance Learning during the Covid-19 Pandemic

Abstract: Distance learning has an impact on decreasing university students’ motivation to learn. Meanwhile, learning motivation is fundamental in the distance learning process. Learning motivation correlates with internal factors such as self-efficacy and emotional intelligence and external factors such as parental social support. This study aimed to find alternative factors that support learning motivation and examine the relationship between self-efficacy, emotional intelligence, and parental social support with lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
(48 reference statements)
0
1
0
1
Order By: Relevance
“…Sejalan dengan penelitian Wardani et al (2021) diperoleh penilaian skor dengan presentase sebesar >81% sehingga media interaktif berbasis e-book pada pembelajaran IPA tergolong kriteria sangat layak. Dengan kategori sangat layak terhadap bahan ajar berbasis e-book akan mengakibatkan semakin mudahnya kegiatan belajar siswa, dalam hal ini dapat memudahkan guru dalam menyampaikan materi dan siswa dalam memahami materi sehingga hasil belajar siswa juga akan semakin baik (Andriani et al, 2022;Muthmainnah & Rohmah, 2022).…”
Section: Tahap Evaluasiunclassified
“…Sejalan dengan penelitian Wardani et al (2021) diperoleh penilaian skor dengan presentase sebesar >81% sehingga media interaktif berbasis e-book pada pembelajaran IPA tergolong kriteria sangat layak. Dengan kategori sangat layak terhadap bahan ajar berbasis e-book akan mengakibatkan semakin mudahnya kegiatan belajar siswa, dalam hal ini dapat memudahkan guru dalam menyampaikan materi dan siswa dalam memahami materi sehingga hasil belajar siswa juga akan semakin baik (Andriani et al, 2022;Muthmainnah & Rohmah, 2022).…”
Section: Tahap Evaluasiunclassified
“…Self-efficacy may make it easier for college students to experience a sense of accomplishment in their studies and motivate their willingness to pursue better academic performance ( Dogan, 2015 ), which may have a positive impact on their motivation to learn. Previous research has found a correlation between self-efficacy and both emotional intelligence and learning motivation ( Andriani et al, 2022 ). Self-efficacy and learning motivation may also be closely linked, although whether self-efficacy is a mediating variable in the relationship between emotional intelligence and learning motivation remains unclear.…”
Section: Introductionmentioning
confidence: 97%
“…According to Bandura’s social cognitive theory, self-efficacy is a subjective self-evaluation and belief derived from an individual’s own experiences ( 7 ), that is, the result of an individual’s evaluation of whether they can successfully complete a certain achievement behavior, which could be divided into three dimensions: magnitude, strength, and generality ( 8 ); After the self-assessment, an individual tends to set appropriate goals based on the evaluation results and determine the plan to achieve them ( 9 ). Previous studies have evidenced that adolescents with high self-efficacy are self-confident and less susceptible to mental disorders when they encounter setbacks, and show higher academic performance ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Andriani et al. showed that self-efficacy has a positive relationship with learning motivation ( 8 ). Strengthening self-efficacy can also improve the learning outcomes of vocational education students ( 12 ).…”
Section: Introductionmentioning
confidence: 99%